A wear-resistant composite ceramic coating for bearings and preparation method thereof
By using a composite ceramic coating on the bearing and using laser cladding technology to form the coating, the problem of wear and corrosion of the bearing during long-term use and humid environments is solved, and the wear and corrosion resistance of the bearing is significantly improved and extended. extended service life.
Patent Information
- Application Number
- CN202411354600.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing bearing coatings are prone to wear and corrosion during long-term use and humid environments, resulting in shorter service life and safety hazards.
A wear-resistant composite ceramic coating for bearings is used. Its raw materials include composite smelting materials, nanographene, titanium powder, yttrium oxide, chromium nitrate, aluminum nitrate, lanthanum zirconate and ethyl orthosilicate. It is applied through laser cladding technology. A ceramic coating is formed on the surface of the bearing's inner ring.
Significantly improves the bonding strength between the ceramic coating and the bearing inner ring, reduces the brittleness of the bonding part, enhances wear and corrosion resistance, and extends the service life of the bearing.
Smart Images

Figure CN118880154B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic coatings, and in particular to a wear-resistant composite ceramic coating for a bearing and a preparation method thereof. Background Art
[0002] Steel materials are widely used in various industrial fields, supporting the rapid development of various industries. However, metal corrosion is very easy to occur in various industrial and natural environments, spreading throughout all areas of the national economy, causing huge losses to the national economy.
[0003] Bearings are important basic parts of the machinery industry. They are mainly made of steel. Their main function is to support the mechanical rotating body, reduce the friction coefficient during its movement, and ensure its rotation accuracy. Bearings are widely used in marine equipment, chemical machinery, medicine, food, textile bleaching and dyeing industries.
[0004] During long-term use, the surface of the bearing is easily worn and corroded, and the surface friction coefficient will also increase, which will not only affect normal use, but also reduce the service life of the bearing. Once a problem occurs, it will lead to a major overhaul of the unit or cause a safety accident. Therefore, how to prepare a bearing coating that can be used for a longer time is a key technical problem that needs to be solved urgently.
[0005] The safety, reliability and stability of bearing operation are extremely important. However, if bearings are used in a humid environment for a long time, they will not only be subject to wear and tear inside the bearings, but also to corrosion from the humid environment and other polluted environments, which will seriously affect the performance of the bearings and shorten their service life. At present, the main means of corrosion protection for bearing surfaces is to apply heavy anti-corrosion coatings. However, such coatings show insufficient properties such as coating strength and wear resistance during service, and it is difficult to maintain the bonding strength with the steel substrate surface.
[0006] Laser cladding is a new surface treatment technology that adds cladding material to the substrate working surface and uses a high-power density laser beam to melt it together with a thin layer on the substrate working surface. TiN coating material has high hardness and low friction coefficient. It is widely used as a surface protection layer for various parts due to its good wear resistance and corrosion resistance. In order to increase the service life of bearings, depositing TiN ceramic coating on bearings is an effective way.
[0007] However, there are currently huge differences in the physical properties (such as thermal expansion coefficient) between ceramics and steel metal substrates. The cladding layer is prone to crack defects, and the coating has insufficient bonding with the steel substrate, resulting in poor wear resistance and corrosion resistance, which seriously affects performance and is difficult to meet the actual needs of the application. Summary of the invention
[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a wear-resistant composite ceramic coating for bearings and a preparation method thereof.
[0009] A wear-resistant composite ceramic coating for a bearing, wherein the raw materials include, by mass, 40-60 parts of a composite smelting material, 1-3 parts of nanographene, 1-3 parts of titanium powder, 1-2 parts of yttrium oxide, 0.1-1 parts of an organic binder, 1-3 parts of chromium nitrate, 1-3 parts of aluminum nitrate, 0.1-0.2 parts of lanthanum zirconate, and 1-3 parts of tetraethyl orthosilicate; the raw materials of the composite smelting material include, by mass percentage, 20-30% nickel, 1-2% borax, 1-3% silicon powder, 1-2% cobalt powder, 1-2% carbon powder, and the balance is iron powder.
[0010] Preferably, the mesh size of the composite smelting material is 100-300 meshes.
[0011] Preferably, the mesh size of the titanium powder is 500-800 mesh.
[0012] Preferably, the organic binder is polyethylene glycol.
[0013] The method for preparing the above-mentioned wear-resistant composite ceramic coating for bearings comprises the following steps:
[0014] S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, ball-milled for 30-40 minutes, dried at 90-100° C., and melted and atomized to obtain a composite smelting material;
[0015] S2, adding chromium nitrate, aluminum nitrate and lanthanum zirconate to an ethanol aqueous solution and stirring for 1-2 hours, adjusting the pH value of the system to 3-4, adding tetraethyl orthosilicate thereto, ultrasonically treating at 70-80°C for 1-2 hours, and then drying the obtained colloid to constant weight, calcining at 1000-1100°C for 10-30 minutes, cooling to room temperature, adding composite smelting material, nanographene, titanium powder and yttrium oxide, and ball milling for 5-6 hours, adding an organic binder and continuing ball milling for 1-2 hours to obtain ceramic powder;
[0016] S3. The inner ring of the bearing is polished with sandpaper, ultrasonically cleaned, and blown dry. Ceramic powder is used as the cladding material, and a ceramic coating is formed on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
[0017] Preferably, in S1, VIGA system is used for melting atomization, and the atomization medium is argon.
[0018] Preferably, in S2, the ultrasonic frequency is 10-20 kHz.
[0019] Preferably, in S3, the thickness of the ceramic coating is 0.15-0.25 mm.
[0020] Preferably, in S3, during the laser cladding process, nitrogen side blowing is used to protect the cladding area, the output power is 1.2-1.5 kW, the spot diameter is 1.5-1.8 mm, the scanning speed is 500-600 mm / min, and the powder feeding rate is 5-10 g / min.
[0021] Preferably, in S3, the flow rate of the side-blowing nitrogen is 5-10 L / min.
[0022] The ceramic coating obtained by the present invention has high bonding strength with the inner ring of the bearing, a dense overall structure of the coating, few cracks at the bonding position, significantly reducing the brittleness of the bonding position with the inner ring of the bearing and increasing its service life. The lanthanum and yttrium elements in the coating cooperate with each other as rare earth elements and are evenly distributed. The coating has excellent wear resistance and corrosion resistance even at high temperatures and has strong practicality.
[0023] The present invention adopts chromium nitrate, aluminum nitrate and lanthanum zirconate as the compound, and tetraethyl orthosilicate is dispersed therein and decomposed to form a sol by controlling process parameters. Chromium nitrate, aluminum nitrate and lanthanum zirconate are uniformly dispersed in the formed three-dimensional nano-network sol, and then high-temperature calcination is performed to promote solid phase reaction to form a complex phase material. The composite material has not only a small difference between the grain boundary and the intracrystalline components, but also excellent corrosion resistance, and can effectively reduce the adhesive wear of the coating, and has excellent wear resistance and friction reduction performance.
[0024] During the laser cladding process, the composite phase material is combined with the composite smelting material to form a fine-sized and evenly distributed reinforcement phase, which has a high bonding strength with the bearing interface and is not easy to fall off; and the addition of nanographene and yttrium oxide compounding promotes small plastic deformation of the coating, further enhancing the wear resistance of the system, and the coating structure has high density. It was found through experiments that the effective thickness of the coating obtained in this application is 0.15-0.25mm, and it can effectively maintain excellent corrosion resistance after salt spray test, and no obvious corrosion behavior is observed on the surface of the 1000h salt spray test.
[0025] After the rough machining of the spherical surface of the inner ring of the bearing of the present invention is completed, a ceramic coating is formed on its surface, which not only improves the working hardness and wear resistance of the bearing and significantly reduces the friction coefficient, but also has excellent corrosion resistance and can meet the long-term use requirements of industries such as marine engineering equipment, chemical machinery (easy to corrode), medicine, food, textile bleaching and dyeing. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a comparison chart of the microhardness at different positions of the ceramic coatings obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 2 The figure is a comparison chart of the average microhardness of the ceramic coatings obtained in Example 5 and Comparative Examples 1-2.
[0028] Figure 3This is a comparison chart of the average friction coefficients of the ceramic coatings obtained in Example 5 and Comparative Examples 1-2 at 20°C and 600°C, respectively.
[0029] Figure 4 The wear rate comparison chart of the ceramic coating obtained in Example 5 and Comparative Examples 1-2 at 20°C and 600°C respectively. DETAILED DESCRIPTION
[0030] The present invention will be further explained below in conjunction with specific embodiments. Example 1
[0031] A wear-resistant composite ceramic coating for a bearing, the raw materials of which include: 400g of 100-mesh composite smelting material, 10g of nanographene, 10g of 500-mesh titanium powder, 10g of yttrium oxide, 1g of polyethylene glycol, 10g of chromium nitrate, 10g of aluminum nitrate, 1g of lanthanum zirconate, and 10g of tetraethyl orthosilicate.
[0032] The raw materials of the composite smelting material include, by mass percentage, 20% nickel, 1% borax, 1% silicon powder, 1% cobalt powder, 1% carbon powder, and the balance is iron powder.
[0033] The method for preparing the above-mentioned wear-resistant composite ceramic coating for bearings comprises the following steps:
[0034] S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, sent into a planetary ball mill, ball milled at a speed of 200 r / min for 30 min, dried at a temperature of 90° C., and sent into a VIGA system for melting and atomization, wherein the atomization medium is argon gas, to obtain a composite smelting material;
[0035] S2. Add chromium nitrate, aluminum nitrate and lanthanum zirconate to a 40% ethanol aqueous solution by mass, stir at a speed of 500 r / min for 1 h, use a 1 mol / L nitric acid solution to adjust the pH value of the system to 3-4, add tetraethyl orthosilicate, and ultrasonically treat at 70°C for 1 h with an ultrasonic frequency of 10 kHz. Then dry the obtained colloid at 120°C to constant weight, calcine at 1000°C for 10 min, cool to room temperature, add composite smelting material, nanographene, titanium powder and yttrium oxide, send to a ball mill for ball milling for 5 h with a ball milling speed of 400 r / min, add polyethylene glycol and continue ball milling for 1 h to obtain ceramic powder;
[0036] S3. The inner ring of the bearing was polished with 200-mesh silicon carbide sandpaper, ultrasonically cleaned with acetone and deionized water, and dried. Ceramic powder was used as the cladding material, and a ceramic coating with a thickness of 0.15 mm was formed on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
[0037] During the laser cladding process, nitrogen (5L / min) side blowing was used to protect the cladding area, the output power was 1.2kW, the spot diameter was 1.5mm, the scanning speed was 500mm / min, and the powder feeding rate was 5g / min. Example 2
[0038] A wear-resistant composite ceramic coating for a bearing, the raw materials of which include: 600g of 300-mesh composite smelting material, 30g of nanographene, 30g of 800-mesh titanium powder, 20g of yttrium oxide, 10g of polyethylene glycol, 30g of chromium nitrate, 30g of aluminum nitrate, 2g of lanthanum zirconate, and 30g of tetraethyl orthosilicate.
[0039] The raw materials of the composite smelting material include, by mass percentage, 30% nickel, 2% borax, 3% silicon powder, 2% cobalt powder, 2% carbon powder, and the balance is iron powder.
[0040] The method for preparing the above-mentioned wear-resistant composite ceramic coating for bearings comprises the following steps:
[0041] S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, sent into a planetary ball mill, ball milled at a speed of 600 r / min for 40 min, dried at a temperature of 100° C., and sent into a VIGA system for melting and atomization, wherein the atomization medium is argon gas, to obtain a composite smelting material;
[0042] S2, adding chromium nitrate, aluminum nitrate and lanthanum zirconate to an ethanol aqueous solution with a mass fraction of 60%, stirring at a speed of 1000r / min for 2h, using a nitric acid solution with a concentration of 2mol / L to adjust the pH value of the system to 3-4, adding tetraethyl orthosilicate thereto, ultrasonically treating at a temperature of 80°C for 2h, the ultrasonic frequency of which is 20kHz, and then drying the obtained colloid at 150°C to constant weight, calcining at a temperature of 1100°C for 30min, cooling to room temperature, adding composite smelting material, nanographene, titanium powder and yttrium oxide, sending to a ball mill for ball milling for 6h, the ball milling speed is 500r / min, adding polyethylene glycol and continuing ball milling for 2h to obtain ceramic powder;
[0043] S3. Use 200-mesh silicon carbide sandpaper to grind the inner ring of the bearing, use acetone and deionized water ultrasonic cleaning in turn, blow dry, use ceramic powder as the cladding material, and form a ceramic coating with a thickness of 0.25 mm on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
[0044] During the laser cladding process, nitrogen (10L / min) side blowing was used to protect the cladding area, the output power was 1.5kW, the spot diameter was 1.8mm, the scanning speed was 600mm / min, and the powder feeding rate was 10g / min. Example 3
[0045] A wear-resistant composite ceramic coating for a bearing, the raw materials of which include: 550g of 150-mesh composite smelting material, 15g of nanographene, 15g of 700-mesh titanium powder, 18g of yttrium oxide, 3g of polyethylene glycol, 25g of chromium nitrate, 15g of aluminum nitrate, 1.7g of lanthanum zirconate, and 15g of tetraethyl orthosilicate.
[0046] The raw materials of the composite smelting material include, by mass percentage, 28% nickel, 1.3% borax, 2.5% silicon powder, 1.2% cobalt powder, 1.7% carbon powder, and the balance is iron powder.
[0047] The method for preparing the above-mentioned wear-resistant composite ceramic coating for bearings comprises the following steps:
[0048] S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, sent into a planetary ball mill, ball milled at a speed of 300 r / min for 37 min, dried at a temperature of 92° C., and sent into a VIGA system for melting and atomization, wherein the atomization medium is argon gas, to obtain a composite smelting material;
[0049] S2, adding chromium nitrate, aluminum nitrate and lanthanum zirconate to an ethanol aqueous solution with a mass fraction of 55%, stirring at a speed of 700r / min for 100min, using a nitric acid solution with a concentration of 1.2mol / L to adjust the pH value of the system to 3-4, adding tetraethyl orthosilicate thereto, ultrasonically treating at a temperature of 77°C for 80min, and an ultrasonic frequency of 18kHz, and then drying the obtained colloid at 130°C to constant weight, calcining at a temperature of 1080°C for 15min, cooling to room temperature, adding composite smelting material, nanographene, titanium powder, and yttrium oxide, sending to a ball mill for ball milling for 340min, the ball milling speed is 420r / min, adding polyethylene glycol and continuing ball milling for 100min, to obtain ceramic powder;
[0050] S3. The inner ring of the bearing is polished with 200-mesh silicon carbide sandpaper, ultrasonically cleaned with acetone and deionized water, blown dry, and ceramic powder is used as the cladding material to form a ceramic coating with a thickness of 0.20 mm on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
[0051] During the laser cladding process, nitrogen (7L / min) side blowing was used to protect the cladding area. The output power was 1.4kW, the spot diameter was 1.6mm, the scanning speed was 580mm / min, and the powder feeding rate was 7g / min. Example 4
[0052] A wear-resistant composite ceramic coating for a bearing, the raw materials of which include: 450g of 240-mesh composite smelting material, 25g of nanographene, 25g of 600-mesh titanium powder, 12g of yttrium oxide, 7g of polyethylene glycol, 15g of chromium nitrate, 25g of aluminum nitrate, 1.3g of lanthanum zirconate, and 25g of tetraethyl orthosilicate.
[0053] The raw materials of the composite smelting material include, by mass percentage, 22% nickel, 1.7% borax, 1.5% silicon powder, 1.8% cobalt powder, 1.3% carbon powder, and the balance is iron powder.
[0054] The method for preparing the above-mentioned wear-resistant composite ceramic coating for bearings comprises the following steps:
[0055] S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, sent into a planetary ball mill, ball milled at a speed of 500 r / min for 33 min, dried at a temperature of 98° C., and sent into a VIGA system for melting and atomization, wherein the atomization medium is argon gas, to obtain a composite smelting material;
[0056] S2, adding chromium nitrate, aluminum nitrate and lanthanum zirconate to an ethanol aqueous solution with a mass fraction of 45%, stirring at a speed of 900r / min for 80min, using a nitric acid solution with a concentration of 1.8mol / L to adjust the pH value of the system to 3-4, adding tetraethyl orthosilicate thereto, ultrasonically treating at a temperature of 73°C for 100min, and an ultrasonic frequency of 12kHz, and then drying the obtained colloid at 140°C to constant weight, calcining at a temperature of 1020°C for 25min, cooling to room temperature, adding composite smelting material, nanographene, titanium powder, and yttrium oxide, sending to a ball mill for ball milling for 320min, the ball milling speed is 480r / min, adding polyethylene glycol and continuing ball milling for 80min, to obtain ceramic powder;
[0057] S3. The inner ring of the bearing is polished with 200-mesh silicon carbide sandpaper, ultrasonically cleaned with acetone and deionized water, blown dry, and ceramic powder is used as the cladding material to form a ceramic coating with a thickness of 0.20 mm on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
[0058] During the laser cladding process, nitrogen (9L / min) side blowing was used to protect the cladding area. The output power was 1.3kW, the spot diameter was 1.7mm, the scanning speed was 520mm / min, and the powder feeding rate was 9g / min. Example 5
[0059] A wear-resistant composite ceramic coating for a bearing, the raw materials of which include: 500g of 200-mesh composite smelting material, 20g of nanographene, 20g of 650-mesh titanium powder, 15g of yttrium oxide, 5g of polyethylene glycol, 20g of chromium nitrate, 20g of aluminum nitrate, 1.5g of lanthanum zirconate, and 20g of tetraethyl orthosilicate.
[0060] The raw materials of the composite smelting material include, by mass percentage, 25% nickel, 1.5% borax, 2% silicon powder, 1.5% cobalt powder, 1.5% carbon powder, and the balance is iron powder.
[0061] The method for preparing the above-mentioned wear-resistant composite ceramic coating for bearings comprises the following steps:
[0062] S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, sent into a planetary ball mill, ball milled at a speed of 400 r / min for 35 min, dried at a temperature of 95° C., and sent into a VIGA system for melting and atomization, wherein the atomization medium is argon gas, to obtain a composite smelting material;
[0063] S2, adding chromium nitrate, aluminum nitrate and lanthanum zirconate to an ethanol aqueous solution with a mass fraction of 50%, stirring at a speed of 800r / min for 90min, using a nitric acid solution with a concentration of 1.5mol / L to adjust the pH value of the system to 3-4, adding tetraethyl orthosilicate thereto, ultrasonically treating at a temperature of 75°C for 90min, the ultrasonic frequency is 15kHz, and then drying the obtained colloid at 135°C to constant weight, calcining at a temperature of 1050°C for 20min, cooling to room temperature, adding composite smelting material, nanographene, titanium powder and yttrium oxide, sending to a ball mill for ball milling for 330min, the ball milling speed is 450r / min, adding polyethylene glycol and continuing ball milling for 90min to obtain ceramic powder;
[0064] S3. The inner ring of the bearing is polished with 200-mesh silicon carbide sandpaper, ultrasonically cleaned with acetone and deionized water, blown dry, and ceramic powder is used as the cladding material to form a ceramic coating with a thickness of 0.20 mm on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
[0065] During the laser cladding process, nitrogen (8L / min) side blowing was used to protect the cladding area. The output power was 1.35kW, the spot diameter was 1.65mm, the scanning speed was 550mm / min, and the powder feeding rate was 8g / min.
[0066] Comparative Example 1
[0067] A wear-resistant composite ceramic coating for a bearing, the raw materials of which include: 500g of 200-mesh composite smelting material, 20g of nanographene, 20g of 650-mesh titanium powder, 15g of yttrium oxide, 5g of polyethylene glycol, 20g of chromium nitrate, 20g of aluminum nitrate, 1.5g of lanthanum zirconate, and 20g of tetraethyl orthosilicate.
[0068] The raw materials of the composite smelting material include, by mass percentage, 25% nickel, 1.5% borax, 2% silicon powder, 1.5% cobalt powder, 1.5% carbon powder, and the balance is iron powder.
[0069] The method for preparing the above-mentioned wear-resistant composite ceramic coating for bearings comprises the following steps:
[0070] S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, sent into a planetary ball mill, ball milled at a speed of 400 r / min for 35 min, dried at a temperature of 95° C., and sent into a VIGA system for melting and atomization, wherein the atomization medium is argon gas, to obtain a composite smelting material;
[0071] S2, adding chromium nitrate and aluminum nitrate to a 50% ethanol aqueous solution by mass, stirring at a speed of 800r / min for 90min, using a 1.5mol / L nitric acid solution to adjust the pH value of the system to 3-4, adding tetraethyl orthosilicate thereto, ultrasonically treating at a temperature of 75°C for 90min, the ultrasonic frequency of which is 15kHz, and then drying the obtained colloid at 135°C to constant weight, adding lanthanum zirconate and mixing evenly, calcining at a temperature of 1050°C for 20min, cooling to room temperature, adding composite smelting material, nanographene, titanium powder, and yttrium oxide, sending to a ball mill for ball milling for 330min, the ball milling speed is 450r / min, adding polyethylene glycol and continuing ball milling for 90min, and obtaining ceramic powder;
[0072] S3. The inner ring of the bearing is polished with 200-mesh silicon carbide sandpaper, ultrasonically cleaned with acetone and deionized water, blown dry, and ceramic powder is used as the cladding material to form a ceramic coating with a thickness of 0.20 mm on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
[0073] During the laser cladding process, nitrogen (8L / min) side blowing was used to protect the cladding area. The output power was 1.35kW, the spot diameter was 1.65mm, the scanning speed was 550mm / min, and the powder feeding rate was 8g / min.
[0074] Comparative Example 2
[0075] A wear-resistant composite ceramic coating for a bearing, the raw materials of which include: 500g of 200-mesh composite smelting material, 20g of nanographene, 20g of 650-mesh titanium powder, 15g of yttrium oxide, 5g of polyethylene glycol, 20g of chromium nitrate, 20g of aluminum nitrate, 1.5g of lanthanum zirconate, and 20g of tetraethyl orthosilicate.
[0076] The raw materials of the composite smelting material include, by mass percentage, 25% nickel, 1.5% borax, 2% silicon powder, 1.5% cobalt powder, 1.5% carbon powder, and the balance is iron powder.
[0077] The method for preparing the above-mentioned wear-resistant composite ceramic coating for bearings comprises the following steps:
[0078] S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, sent into a planetary ball mill, ball milled at a speed of 400 r / min for 35 min, dried at a temperature of 95° C., and sent into a VIGA system for melting and atomization, wherein the atomization medium is argon gas, to obtain a composite smelting material;
[0079] S2, chromium nitrate, aluminum nitrate and lanthanum zirconate were mixed evenly, calcined at 1050°C for 20 min, cooled to room temperature, added with composite smelting material, nanographene, titanium powder and yttrium oxide, sent to a ball mill for 330 min, the ball mill speed was 450 r / min, polyethylene glycol was added and ball milled for 90 min to obtain ceramic powder;
[0080] S3. The inner ring of the bearing is polished with 200-mesh silicon carbide sandpaper, ultrasonically cleaned with acetone and deionized water, blown dry, and ceramic powder is used as the cladding material to form a ceramic coating with a thickness of 0.20 mm on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
[0081] During the laser cladding process, nitrogen (8L / min) side blowing was used to protect the cladding area. The output power was 1.35kW, the spot diameter was 1.65mm, the scanning speed was 550mm / min, and the powder feeding rate was 8g / min.
[0082] A 304 stainless steel plate was used as the bearing inner ring as the substrate, and a ceramic coating with a thickness of 0.20±0.02 mm was formed on the surface of the 304 stainless steel plate according to the raw materials and methods of Example 5 and Comparative Examples 1-2. The ceramic coatings obtained in each group were tested as follows:
[0083] 1. Microhardness test was performed using a microhardness tester with a test load of 4.9 N and a holding time of 15 s. The test was performed every 400 μm along the longitudinal direction of the coating cross section.
[0084] 2. Tribological tests were carried out at 20°C and 600°C using a high-temperature friction and wear testing machine. The wear test parameters were as follows: friction radius 3mm, linear speed 16.88m / min, load 5N, and wear 30min; and a probe-type material surface wear scar measuring instrument was used to measure the wear profile and volume of the sample.
[0085] like Figure 1 and Figure 2 As shown, the microhardness of Example 5 is the highest, which is better than that of Comparative Examples 1-2 (P < 0.05).
[0086] Wear rate = wear volume ÷ (load × sliding distance)
[0087] Wear volume unit is mm 3 , load unit is N, sliding distance unit is m, wear rate unit is mm 3 / (N·m).
[0088] like Figure 3 and Figure 4 As shown, as the temperature increases, the contact surface softens, the wear of each group of ceramic coatings increases significantly, while the friction coefficient decreases. The average friction coefficient and wear rate of Example 5 are always the lowest at both 20°C and 600°C, which is better than Comparative Examples 1-2 (P < 0.05).
[0089] At the same time, according to Figures 1 to 4It can be seen that the interface bonding strength between the ceramic coating and the substrate in Example 5 is high and not easy to fall off, otherwise the wear rate will increase significantly, and the plastic deformation is small.
[0090] The salt spray test machine was used to test the salt spray resistance of the ceramic coatings in the above groups. The pH value was 7 and the mass fraction was 5% NaCl solution as the salt spray medium. The test temperature was 35±2℃ and the spray rate was 80cm / s. 2 The spray volume on the horizontal area is 1-2mL / h, and the experimental period is 1000h. After the test, the surface of each group of ceramic coatings was observed.
[0091] The ceramic coating obtained in Example 5 showed no obvious change, while the surface of the ceramic coating obtained in Comparative Example 1 became darker, and the surface of the ceramic coating obtained in Comparative Example 2 not only became darker, but also had gray corrosion products.
[0092] The applicant believes that the reasons for the above test results are: the present invention uses chromium nitrate, aluminum nitrate and lanthanum zirconate to compound, and tetraethyl orthosilicate is dispersed therein and decomposed to form a sol by controlling process parameters, and chromium nitrate, aluminum nitrate and lanthanum zirconate are evenly dispersed in the formed three-dimensional nano-network sol, and then high-temperature calcination is used to promote solid-phase reaction to form a complex phase material, which not only has a small difference between the grain boundary and the intracrystalline composition, but also has excellent corrosion resistance, and can effectively reduce the adhesive wear of the coating, and has excellent wear resistance and friction reduction performance. In the laser cladding process, the complex phase material is combined with the composite smelting material to form a small-sized, evenly distributed reinforcement phase, which has a high bonding strength with the bearing interface and is not easy to fall off; and the addition of nanographene and yttrium oxide compounding promotes small plastic deformation of the coating, further enhancing the wear resistance of the system, and the coating structure has high density.
[0093] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A wear-resistant composite ceramic coating for a bearing, characterized in that: The raw materials include, by mass: 40-60 parts of composite smelting material, 1-3 parts of nanographene, 1-3 parts of titanium powder, 1-2 parts of yttrium oxide, 0.1-1 parts of organic binder, 1-3 parts of chromium nitrate, 1-3 parts of aluminum nitrate, 0.1-0.2 parts of lanthanum zirconate, and 1-3 parts of tetraethyl orthosilicate; The raw materials of the composite smelting material include, by mass percentage, 20-30% nickel, 1-2% borax, 1-3% silicon powder, 1-2% cobalt powder, 1-2% carbon powder, and the balance is iron powder; The method for preparing the wear-resistant composite ceramic coating for the bearing comprises the following steps: S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, ball-milled for 30-40 minutes, dried at 90-100° C., and melted and atomized to obtain a composite smelting material; S2, adding chromium nitrate, aluminum nitrate and lanthanum zirconate to an ethanol aqueous solution and stirring for 1-2 hours, adjusting the pH value of the system to 3-4, adding tetraethyl orthosilicate thereto, ultrasonically treating at 70-80°C for 1-2 hours, and then drying the obtained colloid to constant weight, calcining at 1000-1100°C for 10-30 minutes, cooling to room temperature, adding composite smelting material, nanographene, titanium powder and yttrium oxide, and ball milling for 5-6 hours, adding an organic binder and continuing ball milling for 1-2 hours to obtain ceramic powder; S3. The inner ring of the bearing is polished with sandpaper, ultrasonically cleaned, and blown dry. Ceramic powder is used as the cladding material, and a ceramic coating is formed on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
2. The wear-resistant composite ceramic coating for bearings according to claim 1, characterized in that: The mesh size of the composite smelting material is 100-300 meshes.
3. The wear-resistant composite ceramic coating for bearings according to claim 1, characterized in that: The mesh size of titanium powder is 500-800 mesh.
4. The wear-resistant composite ceramic coating for bearings according to claim 1, characterized in that: The organic binder is polyethylene glycol.
5. A method for preparing a wear-resistant composite ceramic coating for a bearing as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1. Nickel powder, borax, silicon powder, cobalt powder, carbon powder and iron powder are mixed evenly, ball-milled for 30-40 minutes, dried at 90-100° C., and melted and atomized to obtain a composite smelting material; S2, adding chromium nitrate, aluminum nitrate and lanthanum zirconate to an ethanol aqueous solution and stirring for 1-2 hours, adjusting the pH value of the system to 3-4, adding tetraethyl orthosilicate thereto, ultrasonically treating at 70-80°C for 1-2 hours, and then drying the obtained colloid to constant weight, calcining at 1000-1100°C for 10-30 minutes, cooling to room temperature, adding composite smelting material, nanographene, titanium powder and yttrium oxide, and ball milling for 5-6 hours, adding an organic binder and continuing ball milling for 1-2 hours to obtain ceramic powder; S3. The inner ring of the bearing is polished with sandpaper, ultrasonically cleaned, and blown dry. Ceramic powder is used as the cladding material, and a ceramic coating is formed on the surface of the inner ring of the bearing through synchronous powder feeding laser cladding.
6. The method for preparing the wear-resistant composite ceramic coating for bearings according to claim 5, characterized in that: In S1, VIGA system was used for melting atomization, and the atomization medium was argon.
7. The method for preparing the wear-resistant composite ceramic coating for bearings according to claim 5, characterized in that: In S2, the ultrasound frequency is 10-20kHz.
8. The method for preparing the wear-resistant composite ceramic coating for bearings according to claim 5, characterized in that: In S3, the thickness of the ceramic coating is 0.15-0.25 mm.
9. The method for preparing the wear-resistant composite ceramic coating for bearings according to claim 5, characterized in that: In S3, during the laser cladding process, nitrogen side blowing was used to protect the cladding area, the output power was 1.2-1.5kW, the spot diameter was 1.5-1.8mm, the scanning speed was 500-600mm / min, and the powder feeding rate was 5-10g / min.
10. The method for preparing the wear-resistant composite ceramic coating for bearings according to claim 9, characterized in that: In S3, the side blowing nitrogen flow rate is 5-10L / min.
Citation Information
Patent Citations
Graphene oxide coated ceramic particle corrosion-resistant gradient coating and preparation method thereof
CN114477965A
Preparation method of seamless steel tube piercing plug surface protective coating
CN116426919A